Association between Bcl-2 expression and tumor recurrence in cervical cancer: A matched case-control study - Sumonmal Manusirivithaya (2018)
Objectives.: To evaluate the association between bcl-2 expression, some pathological factors (lymph-vascular space invasion (LVSI), tumor grade, depth of stromal invasion), and tumor recurrence in cervical cancer. Methods.: A matched case-control study was performed in cervical cancer patients who underwent radical hysterectomy and were found to have negative lymph node between January 1992 and June 1998 in Bangkok Metropolitan Administration Medical College and Vajira Hospital and Maharaj Nakorn Chiangmai Hospital, Thailand. Cases were 32 patients who had tumor recurrence within 5 years after surgery. Controls were 63 patients who were disease free for at least 5 years after surgery. Cases and controls were matched for age, stage, histology, and tumor size. All except one case, who had only one matching control, had two controls. Paraffin-embedded cervical cancer tissues of cases and controls were immunohistochemical stained for bcl-2. Results.: Bcl-2 positive was demonstrated in 43.7% of tumor from recurrent cases, which was not different from 50.8% from non-recurrent controls (P = 0.378). Tumor grade and LVSI had significant association with tumor recurrence. From multivariable analysis, the patients with grade 2-3 tumors had the odds ratio of 6.9 for recurrence compared to patients with grade 1 tumors. The patients whose tumors had LVSI had the recurrent odds ratio of 5.4 compared to those without LVSI. Conclusions.: There was no association between bcl-2 expression and tumor recurrence in cervical cancer, while tumor grade and LVSI had significant association with tumor recurrence. © 2005 Elsevier Inc. All rights reserved.